Effect of organic inputs and growing conditions on quality parameters of strawberry (Fragaria × ananassa) - HAZARIKA, JAHNABI; BORTHAKUR, PRITOM KUMAR; PATGIRI, DILIP KUMAR (The Indian Journal of Agricultural Sciences, 2025)
The field experiment was conducted during 2020–2022 at Assam Agricultural University, Jorhat, Assam to evaluate the effect of organic inputs and growing conditions on quality parameters of strawberry (Fragaria × ananassa Duch.). The experiment was laid out in a factorial randomized block design (F-RBD) replicated thrice comprising of five treatments [FYM @180 g/plant (T1), rock phosphate @4.50 g/plant + microbial consortium @0.063 g/plant (T2), T2 + vermicompost @45 g/plant (T3), T2 + enrich compost @45 g/plant (T4) and T2 + poultry manure @45 g/plant (T5)] under four different growing conditions [rain shelter with insect proof net (S1) (top covered with 200 micron UV film and side wall of 40 mesh net), rain shelter without insect proof net (S2), net house (50% shade) i.e. S3 and open condition (S4)]. Quality parameters in terms of higher TSS (9.09 ºBrix), reducing sugar (4.78%), non reducing sugar (3.27%), TSS/Acid ratio (23.59%), total sugar (8.05%), ascorbic acid (54.72 mg/100 g), anthocyanin content (46.30 mg/100 g) and minimum titratable acidity (0.38%) were recorded in treatment combination of T3S1 (vermicompost @45 g/plant + rock phosphate @4.5 g/plant + microbial consortium @0.063 g/plant in growing condition of insect proof net covered with 200 micron UV film on top and 40 mesh net in side.